Hubungan Sumber Informasi Dengan Tingkat Pengetahuan Remaja Puteri Tentang Pijat Akupresure Saat Menstruasi - Sari, Ossie Happina; Maesaroh, Maesaroh (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2022)
Problems felt by adolescents related to menstruation are dysmenorrhea 67.2% and premenstrual syndrome (PMS) 63.1%. Dysmenorrhea is the most common gynecological complaint among adult women and adolescents. This needs to be considered because it will cause discomfort in physical activity. The incidence of dysmenorrhea in the world is very large, on average more than 50% of women experience primary dysmenorrhea. This study aims to determine the relationship between sources of information and the level of knowledge of young women about acupressure massage during menstruation. This research uses a type of analytic survey research with a cross sectional design. The analysis used was bivariate analysis with the Spraeman rank correlation test. The results of the bivariate analysis obtained a p-value of 0.009 which means that there is a relationship between sources of information and knowledge of young women about acupressure massage during menstruation. It is hoped that the school can work together with the health center or other parties in an effort to provide counseling about health to adolescents so that adolescent awareness and knowledge about health, especially regarding acupressure massage in reducing dysmenorrhea as a non-pharmacological therapy can increase adolescent knowledge.